2021
DOI: 10.1111/mice.12799
|View full text |Cite
|
Sign up to set email alerts
|

Deep generative Bayesian optimization for sensor placement in structural health monitoring

Abstract: Optimal sensor placement (OSP) is essential for effective structural health monitoring (SHM). More recently, deep learning algorithms have shown great potential in sensor-based SHM. However, existing optimization frameworks, such as population-based algorithms, are often not suited for data-driven SHM. Evaluating a number of sensor layouts includes training on large datasets, which is computationally expensive. This paper proposes deep generative Bayesian optimization (DGBO) as a solution for a parallel optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…It allows itself to concentrate on those regions of the dimensional space that it considers will provide the most hopeful validation scores by selecting its value, also known intelligently. This method often needs fewer iterations to reach the ideal set of hyperparameter values [16]. Most significantly, it ignores those regions of the dimensional space that it thinks won't contribute anything.…”
Section: ) Bayesian Optimizationmentioning
confidence: 99%
“…It allows itself to concentrate on those regions of the dimensional space that it considers will provide the most hopeful validation scores by selecting its value, also known intelligently. This method often needs fewer iterations to reach the ideal set of hyperparameter values [16]. Most significantly, it ignores those regions of the dimensional space that it thinks won't contribute anything.…”
Section: ) Bayesian Optimizationmentioning
confidence: 99%
“…Zou et al 28 explored deep neural network approaches for detecting pixel‐wise patterns of ancient buildings in China. Sajedi and Liang 29 proposed the use of deep generative Bayesian optimization for searching optimal sensor placement in the sensor‐based SHM. Case studies showed that generative machine learning achieves approximately 10% better performance compared to a benchmark genetic algorithm (GA).…”
Section: Related Workmentioning
confidence: 99%
“…It can potentially provide information regarding the existence, location, type, and extent of the damage. The proposed supervised SHM methods include artificial neural networks (de Lautour & Omenzetter, 2009;Gonzalez & Zapico, 2008;Oh et al, 2017), support vector machines (SVM; Kim et al, 2013;Liang et al, 2018;Sajedi & Liang, 2020a), decision trees (Alves et al, 2015), convolutional neural networks (CNNs; Abdeljaber et al, 2018;Sajedi & Liang, 2020b, 2021a, 2021b, 2021c, and vision-based SHM methods (Gao & Mosalam, 2018;Liang, 2019;Sajedi & Liang, 2019;Sirca & Adeli, 2018). However, acquiring damaged condition data is practically difficult, as structures tend to have different structural properties and site conditions.…”
Section: Introductionmentioning
confidence: 99%